PENYELESAIAN PEMBIAYAAN BERMASALAH MELALUI PARATE EKSEKUSI OBJEK JAMINAN FIDUSIA PADA PT. PEGADAIAN (PERSERO) CABANG MEDAN UTAMA - MAURITS MR SITOHANG; RAMLI SIREGAR; WINDHA WINDHA (TRANSPARENCY, 2013)
Fiduciary agreement is defined as a contract whereby a person, as a debtor (fiduciary assignor party) agrees with another person, the creditor (the fiduciary assignee party) which is mostly a credit institution or similar regulated entity, on the transfer of ownership of moveable assets constituting a fiduciary estate to the aforementioned fiduciary subject to obligations determined by the parties. This is why this agreement also called as the fiduciary transfer of ownership. This kind of agreement represent a less costly and more efficient choice, as the creditor did not have to keep and taking care of the assets, while the debtor still maintains the possession and able to make use of the encumbered assets. In other words, only the legal right of ownership of the assets are temporarily transferred to the hand of a creditor as security / guarantee for the debtor obligations, until the debt is repaid. For these reason, such agreement are considered to be a useful alternatives in arrangement of a credit facilities for both credit institution, in this case PT. Pegadaian (Persero) Cabang Medan Utama and their customer. This research is meant to see how the direct execution on a fiduciary guarantee as a settlement of a non-performing loan on a fiduciary agreement at PT. Pegadaian (Persero) Cabang Medan Utama through a juridical approach using a methods that focused on the legal rules related the problems, with the qualitative data analysis to the laws with theorical concepts, opinions of experts, and other legislations relating to this study, and then to be compared with the field data. Execution by using an executorial title must be carried out by a civil lawsuit filed to the courthouse, which is then will be titled by the court of justice to proceed the execution, according to the courthouse’ verdict. Fiduciary transfer of ownership, prior to the Law No. 42 of 1999 concerning Fiduciary Transfer entitled the creditor the right to directly executed the guaranteed assets and then allowing the creditor to sell the goods to satisfy his debt, followed by returning what remains from the proceeds of the sale to the debtor.   Kata Kunci : Parate Eksekusi, Jaminan Fidusia, Pengurus.